Mekanisme Program Makanan Bergizi Gratis Pada Penggunaan Anggaran Dan Tanggung Jawab Keuangan Menurut Perspektif Hukum Administrasi Negara - Ferly haris (Jurnal Kedaulatan Hukum, 2026)
This study focuses its review on how the procedural aspects of the Free Nutritious Meal Program are regulated within the framework of State Administrative Law (Hukum Administrasi Negara - HAN). Specifically, the research aims to delineate the budget utilization mechanism and the financial accountability system inherent in the implementation of this large-scale national program. The Free Nutritious Meal Program, as a massive public policy, demands high transparency and accountability in the management of state funds. ​The method employed is normative legal research using a conceptual and statutory approach (statute approach). Primary legal sources analyzed include legislation related to state finance, government procurement regulations, and implementing regulations concerning public policy. ​The results of the analysis indicate that the implementation of the program must adhere to the principle of legality and comply with technical administrative rules. The program's budget utilization is subject to the control of state administrative officials (such as the Authority Holder for Budget Use/KPA) and must refer to government procurement regulations to ensure efficiency and corruption prevention. Furthermore, financial accountability is measured by adherence to reporting procedures and administrative justification. It is concluded that compliance with the principle of accountability and the principle of legal certainty in budget governance is a key prerequisite for the program to be administratively valid and not violate HAN provisions, while also ensuring supervision by state audit institutions.